Interesting interstitial Paramesochridae (Copepoda: Harpacticoida): Maliithipon wellsi gen. et sp. nov. from the Philippines, M. aberrans (Mielke, 1984) comb. nov. from Panama, and M. cf. aberrans (Mielke, 1984) from the Azores. - Cottarelli, V. & M.C. Bruno. (In: Huys, R. (ed.). Systematics and Taxonomy of Harpacticoid Copepods—A Commemorative Volume in Honour of Prof. John B.J. Wells, Zootaxa, 569 pp., 2021)
We propose and describe a new genus of interstitial Paramesochridae, Maliithipon gen. nov., to accommodate three species. Maliithipon wellsi sp. nov., type species of the genus, is described based on specimens collected in two sandy beaches in Isla Verde, the Philippines. Apodopsyllus aberrans Mielke, 1984a described from Panama, is allocated to the herein erected genus as Maliithipon aberrans (Mielke, 1984a) comb. nov. Maliithipon cf. aberrans is described, based on specimens collected in the Azores and previously identified as Apodopsyllus aberrans. The new genus is characterized by several distinct morphological features: mandible with uniramous, 2-segmented palp and gnathobase with thin and pointed teeth; maxillule with reduced armature, lacking endopod and exopod; maxilla large, with three syncoxal endites and endopod with reduced setal number; P5 very reduced in both sexes; caudal rami with six setae, two of which (setae III and VI) transformed; pseudoperculum well-developed, with four-lobed distal margin. The new genus is included in the subfamily Paramesochrinae Lang, 1944 and in the genus-group Scottopsyllus (sensu Huys, 1987). It has strong affinities with Leptopsyllus (Leptopsyllus) platyspinosus Mielke, 1984b and Wellsopsyllus (Intermediopsyllus) smirnovi (Kunz, 1992), which are considered as species inquirendae in this paper. Some remarks on the ecology and geonemy of the three studied species are provided. We also list the accompanying Paramesochridae obtained from the two new collecting sites of the genus, and all the genera of Paramesochridae recorded from other sites in the Philippines during the same survey.